2010
DOI: 10.1007/s12262-010-0164-7
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Atypical Mycobacterial Infection after Laparoscopic Surgery

Abstract: Atypical mycobacterial infections at the laparoscopic port site are a frequent problem encountered in patients undergoing laparoscopic surgery. In this study we concentrate on the clinical diagnosis, management and prevention of this problem. In this series we assess 19 patients presenting with port hole infections after laparoscopic surgery and were treated with a combination of oral clarithromycin and ciprofloxacin. Seven patients who had persistent nodules were given injections of amikacin directly into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 13 publications
3
43
0
Order By: Relevance
“…This is in contradiction to some studies where complete cure has been reported in one to three months only. [4] However the studies conducted by Mary A et al and Amit K S et al are in agreement with our study. [8,6] We used intralesional amikacin in only two cases wherein the initial response to the chemotherapy was not significant.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in contradiction to some studies where complete cure has been reported in one to three months only. [4] However the studies conducted by Mary A et al and Amit K S et al are in agreement with our study. [8,6] We used intralesional amikacin in only two cases wherein the initial response to the chemotherapy was not significant.…”
Section: Discussionsupporting
confidence: 93%
“…Erroneous sterilization of the laparoscopic instruments has frequently resulted in the hospital out breaks of port site infections following laparoscopic surgery. [4] Early identification and diagnosis is critical to the successful outcome as these bacteria do not respond to the conventional anti mycobacterial treatment and second line chemotherapy is the foremost management option. [5] Strict adherence to the recommended sterilization protocol is a must for prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, mechanical cleaning of blood and charred tissue that accumulates in the joints of the instruments are also not done properly after surgery. Hence, these contaminated instruments during the surgical process leave endospores on the subcutaneous tissue which germinates and after an incubation period of 3-4 wk clinical symptoms appear [14].…”
Section: Discussionmentioning
confidence: 99%
“…Number of factors may be responsible for this sudden spurt: the instruments that we are using presently have worn out and cannot be thoroughly dismantled and hence cannot be properly cleaned; nonavailability of ultrasonic cleaners; the practice of using personal instruments (which are often used in the private setup as well) to supplement the faulty ones in hospital; disinfection with 2 % glutaraldehyde for 20 min and cleansing them with boiled tap water prior to use; and the overall increase in the number of laparoscopic procedures (consequently less attention to sterilization). The only way to prevent this harassing problem is to keep a strict vigil on the quality of instruments, to avoid sharing of instruments with those used in gynecological and urological practice, use 3.4 % glutaraldehyde for at least 8 h for sterilization and autoclaved water for cleansing, changing glutaraldehyde solution after a maximum of 100 cycles, and autoclaving metallic cannula [27,28].…”
Section: Discussionmentioning
confidence: 99%